Ардын зарга нь улс төрийн оролцоооны нэгэн хэлбэр мөн - Тамир, Чүлтэмсүрэн (Historia Mongolarum, 2003)
This is a study of the petition as form participation of Mongols in political life. The study illustrates the content analyses, based on historical origins of petition in traditional Mongolian society. The public petiton is expression of general tendency of politics. The majority of the petions had economical motives.